2019
DOI: 10.1002/jsfa.9534
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐assisted development of biofunctional polyphenol‐enriched buckwheat protein: physicochemical properties, in vitro digestibility, and antioxidant activity

Abstract: BACKGROUND During the last decade buckwheat was reported to have positive health effects. The present study investigated a high‐polyphenol buckwheat protein (Fagopyrum esculentum Moench) prepared by enzyme‐assisted processing, together with its physicochemical properties, in vitro digestibility, and antioxidant activity. RESULTS Buckwheat protein prepared from the synergistic enzymatic action of α‐amylase and amyloglucosidase (E‐BWP) had much higher polyphenol content than buckwheat protein prepared by isoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A recent study found that the buckwheat protein contents decreased from the exterior to the interior parts of the groats [109]. Significantly higher content of amino acids, fatty acids, polyphenols, and flavonoids was found in the bran of Tartary buckwheat, compared to the flour [110].…”
Section: Millingmentioning
confidence: 94%
“…A recent study found that the buckwheat protein contents decreased from the exterior to the interior parts of the groats [109]. Significantly higher content of amino acids, fatty acids, polyphenols, and flavonoids was found in the bran of Tartary buckwheat, compared to the flour [110].…”
Section: Millingmentioning
confidence: 94%
“…melanoidin-based) products and, at the time of precipitation, the coprecipitation of other compounds, thus leading to coextraction of impurities. [37][38][39] To avoid most of these problems, many researchers choose to use a pH less than or equal to 9 because proteins isolated at these pH values have excellent physicochemical characteristics, including purity, techno-functional and thermal properties. [40][41][42] Alternatively, choosing other extraction methods, such as enzymatic or physical methods, may provide other advantages.…”
Section: Solubility and Extraction Of The Native Amaranth Buckwheat A...mentioning
confidence: 99%
“…lysinoalanine), an increase in Maillard reactions (because of a high pH) resulting in dark colored (i.e. melanoidin‐based) products and, at the time of precipitation, the coprecipitation of other compounds, thus leading to coextraction of impurities 37‐39 …”
Section: Solubility and Extraction Of The Native Amaranth Buckwheat A...mentioning
confidence: 99%
“…The final cytotoxic effects arise from not only the levels of bioactive substances, but also as a function of the synergistic actions among these. Thus, buckwheat protein-rich by-products are a good source of bioactive substances [25][26][27][28][29]. However, in-vitro antiproliferative effects on cancer cells do not always predict health-promoting effects, as the impacts must also be studied and confirmed in vivo.…”
Section: Lysinementioning
confidence: 99%
“…The buckwheat grain is the source of biofunctional peptides [28,[57][58][59][60][61], which are fermented in the process of malting [62] and during the preparation of buckwheat beer or distillation products [63,64].…”
Section: Bioactivity Of Buckwheat Peptidesmentioning
confidence: 99%